2018
DOI: 10.1063/1.5000914
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-like layers as promising chemiresistive sensing material for detection of alcohols at low concentration

Abstract: In the manifold of materials for Volatile Organic Compound (VOC) sensing, graphene related materials (GRMs) gain special attention thanks to their versatility and overall chemico-physical tunability as a function of specific applications. In this work, the sensing performances of graphene-like (GL) layers, a new material belonging to the GRM family, are tested against ethanol and n-butanol. Two typologies of GL samples were produced by employing two different approaches and tested in view of their application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
1
30
2
Order By: Relevance
“…GL layers exhibited a response toward ethanol, expressed as normalized relative variation of conductance, around 3% and toward n-butanol around 0.5% (Fig. 4) [27]. The comparison of the experimental results with those reported by literature showed that GL films are promising candidate for the detection of low concentration of ethanol at room temperature [27].…”
Section: Graphene-like (Gl) Layers and Ultrathin (Gl) Films [24-27]mentioning
confidence: 63%
See 4 more Smart Citations
“…GL layers exhibited a response toward ethanol, expressed as normalized relative variation of conductance, around 3% and toward n-butanol around 0.5% (Fig. 4) [27]. The comparison of the experimental results with those reported by literature showed that GL films are promising candidate for the detection of low concentration of ethanol at room temperature [27].…”
Section: Graphene-like (Gl) Layers and Ultrathin (Gl) Films [24-27]mentioning
confidence: 63%
“…4) [27]. The comparison of the experimental results with those reported by literature showed that GL films are promising candidate for the detection of low concentration of ethanol at room temperature [27].…”
Section: Graphene-like (Gl) Layers and Ultrathin (Gl) Films [24-27]mentioning
confidence: 65%
See 3 more Smart Citations